THE EFFECT OF FORTIFICATION OF BRANDS AND CHITOSAN ON TEMPEH ON FIBER LEVELS AND PROBIOTIC BACTERIA GROWTH - Nunung Kurniasih; Farah Dinna; Vina Amalia; Diana Widiastuti (Helium: Journal of Science and Applied Chemistry, 2021)
Tempeh is a food made from soybean seeds processed through fermentation using Rhizopus sp. This processed food in the form of tempeh contains various nutrients that the body needs such as protein, fat, carbohydrates, and minerals but does not contain enough fiber. Therefore, fortification of rice bran and chitosan was carried out on tempeh. Rice bran is a by-product of rice milling which has a high fiber content. While chitosan is chitin that has removed the acetyl group. Chito-oligosaccharides (COS) contained in chitosan can act as natural prebiotics, preservatives, antimicrobials, lower cholesterol levels and are immunostimulants. The purpose of this study was to determine the fiber content and growth of the probiotic bacteria Lactobacillus acidophilus in soybean tempeh (A), rice bran (B), chitosan (C), the ratio of soybean tempeh: rice bran (6: 3) + 2% chitosan (D) and the ratio of soybean tempeh: bran (6: 2) + 2% chitosan (E). The method used for the analysis of fiber content was gravimetric, while the growth of probiotic bacteria Lactobacillus acidophilus was used to determine the potential of prebiotics contained in samples A, B, C, D, and E. The results obtained in this study were fortification of rice bran and chitosan in tempeh had high levels of fiber and the number of probiotic bacteria cells was higher than soybean tempeh. The higher the bran added, the higher the fiber content and the number of probiotic bacterial cells. while the growth of probiotic bacteria Lactobacillus acidophilus was used to determine the potential of prebiotics contained in samples A, B, C, D, and E. The results obtained in this study were bran and chitosan fortifications in tempeh had higher fiber content and cell counts of probiotic bacteria than soybean tempeh. The higher the bran added, the higher the fiber content and the number of probiotic bacterial cells. while the growth of probiotic bacteria Lactobacillus acidophilus was used to determine the potential of prebiotics contained in samples A, B, C, D, and E. The results obtained in this study were bran and chitosan fortifications in tempeh had higher fiber content and cell counts of probiotic bacteria than soybean tempeh. The higher the bran added, the higher the fiber content and the number of probiotic bacterial cells.